Techno-economic analysis of enzymatic biodiesel co-produced in palm oil mills from sludge palm oil for improving renewable energy access in rural areas. (15th March 2022) - Ng, Wei Zhe; Obon, Aaron Anthony; Lee, Chin Loong; Ong, Yi Hui; Gourich, Wail; Maran, Kireshwen; Tang, Dennis Boon Yong; Song, Cher Pin; Chan, Eng-Seng
Abstract: To date, irregularity and lack of power supply remain a global problem in the rural areas of underdeveloped and developing countries. This paper proposes a new concept for rural electrification by using palm oil mills to co-produce biodiesel from sludge palm oil. We performed a case study based on a medium-sized palm oil mill in Central Kalimantan. Approximately 2.5 tonnes of biodiesel could be produced daily using an enzymatic batch process and potentially support around 1, 375 households of 4 people each in the surrounding areas. Subsequently, we performed a techno-economic assessment to study the commercial feasibility of the concept for rural electrification using the enzymatic biodiesel as opposed to commercial diesel. A 10% price deduction was applied to incentivize the local community to use the co-produced biodiesel. From our analysis, the rural electrification concept was found to be commercially viable with a return on investment of 29% and a breakeven period of less than 4 years of operation. Barring the short-term impacts of the COVID-19 pandemic and the price fluctuations of diesel and crude palm oil, the long-term commercial prospect of this rural electrification concept is attractive as it financially benefits both the rural community and the mill operators. Graphical abstract: Image 1 Highlights: Co-production of biodiesel in palm oil mills for rural electrification was proposed. Biodiesel is produced from sludge palm oil using Eversa® Transform 2.0 lipase. Daily biodiesel production capacity of 2.5 tonnes can support 1, 375 households. ROI of 29% and breakeven period of <4 years based on 10% deducted biodiesel price. The impact of COVID-19 pandemic on the project's commercial prospect was discussed.